Unlocking energy innovation [ how America can build a low-cost, low-carbon energy system - Lester, Richard K. [ (Richard Keith)] , 1954-; Hart, David M. , 1961- (MIT Press, 2012)
"The authors outline three waves of energy innovation to reveal how America can speed up the introduction of new technologies and business models and accelerate deployment on a massive scale"--Provided by publisher.